Public Relations Management in Africa Volume 2
XXIX, 261 p. 4 illus.
Keywords: This two-part volume book examines current pedagogical modules, research directions and other emerging issues in public relations and communication management in Africa. In comparison to its Western and Asian counterparts, the literature on public relations management in Africa is limited, and much of it is examined through the lenses of Western philosophies and pedagogies that do not generally resonate with Africa's socioeconomic, political, and cultural contexts. This book aims to change that. Volume 2 brings together African scholars, moving beyond organizational impacts, to share wider theoretical and practical perspectives on the practice of public relations on the continent. Through conceptual discussions and empirical analyses, this volume demonstrates how Africa is gradually emerging from the shadows of Western public relations scholarship by building a body of knowledge and reflecting on developments in public relations management on the continent. Thechapters covered include a discussion on the current landscape of public relations scholarship and practice in Africa, public relations and identity management, how public relations responds to the challenges of health communication, and the future of public relations in Africa in light of globalization and technological advancement, coupled with the many technological challenges the continent continues to face. Albert A. Anani-Bossman (PhD) is a lecturer and Ag. Head of the Department of public relations in the Faculty of Public Relations, Advertising & Marketing, Ghana Institute of Journalism. Takalani E. Mudzanani is a professor of communication science at the University of South Africa (UNISA). Cornelius B. Pratt is Professor Emeritus of Global Communication and Leadership in the Lew Klein College of Media and Communication at Temple University in Philadelphia, United States. Isaac A. Blankson is a professor of communication and public relations and the president of the African University College of Communications (AUCC). .